Evaluation of macular and optic nerve head parameters in amblyopic eyes: An optical coherence tomography study. Issue 4 (July 2022) - Guagliano, Rosanna; Barillà, Donatella; Bertone, Chiara; Montescani, Silvia; Verticchio Vercellin, Alice C; Arpa, Cristina; Tinelli, Carmine; De Angelis, Giovanni; Quaranta, Luciano
Purpose: To evaluate morphological differences in retinal nerve fibers layers (RNFL), optic nerve head (ONH), ganglion cell complex (GCC), and macular thickness between amblyopic and normal eyes from spectral domain optical coherence tomography (SD-OCT). Methods: Of 234 eyes of 117 children, four groups emerged: group A (162 eyes of 81 non-amblyopic subjects); group B (32 fellow eyes of 32 subjects with monolateral amblyopia); group C (32 amblyopic eyes of 32 subjects affected by monolateral amblyopia); group D (8 amblyopic eyes of 4 subjects with bilateral amblyopia). Patients underwent SD-OCT for ONH parameters, RNFL, GCC and macular thickness, retina map, and ONH scan quality index (SQI). Two-sided p values <0.05 were taken as statistically significant. (Analysis: STATA v.13). Results: Parameters with a significant difference between groups ( p  < 0.005) with their Standard Deviation (SD) are presented: rim area, 2.08 (0.49) mm 2 in group A and 1.76 (0.68) mm 2 in group C; disk area, 2.43 (0.45) mm 2 in group A and 2.02 (0.71) mm 2 in group C; central macular thickness, 250.99 (19.74) µm in group A and 267.16 (23.52) µm in group C; nerve fiber ONH SQI, 62.82 (13.15) in group A, 51.26 (15.55) in group C, 48.29 (14.37) in group D; retina map SQI, 63.34 (10.34) in group A and 57.34 (9.84) in group C. For other parameters no significant difference was observed ( p  > 0.005). Conclusions: Amblyopia may influence optic nerve morphology, central macular thickness, and OCT scan quality. RNFL and GCC are not affected by monolateral amblyopia.